The Association Between Fast-Food Consumption and Physical Activity with Overweight Occurrence at School Among 9-11-Year-Old Children in Cakung Payangan Bekasi (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2020)
Overweight occurs because of excessive energy intake stored in the form of fat tissue. The national prevalence of overweight and obesity among children aged 5-12 years old was 10.8% and 8.8%, respectively. Several factors are responsible for increasing the prevalence of overweight, including food consumption and physical activity. The purpose of this study was to examine the association between fast-food consumption and physical activity with the overweight occurrence among school-aged children in Cakung Payangan, Bekasi. This is a cross-sectional study with a total of 80 students recruited through a simple random sampling method. There was a significant association between fast-food consumption and overweight (p = 0.013, CI 95% = 1,420 – 10,977). Also, there was a significant association between physical activity and overweight (p = 0.027, CI 95% = 1,023 – 74,825). Frequent fast-food consumption and mild physical activity have a significant relationship with overweight occurrence among school-aged children.